1996
DOI: 10.1021/bi960507f
|View full text |Cite
|
Sign up to set email alerts
|

Backbone Dynamics of the C-Terminal Domain of Escherichia coli Topoisomerase I in the Absence and Presence of Single-Stranded DNA

Abstract: The backbone dynamics of the C-terminal DNA-binding domain of Escherichia coli topoisomerase I has been characterized in the absence and presence of single-stranded DNA by NMR spectroscopy. 15N spin-lattice relaxation times (T1), spin-spin relaxation times (T2), and heteronuclear NOEs were determined for the uniformly 15N-labeled protein. These data were analyzed by using the model-free formalism to derive the model-free parameters (S2, tau e, and R(ex)) for each backbone N-H bond vector and the overall molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 22 publications
10
76
2
1
Order By: Relevance
“…Thus, separation of the backbone entropy term from other terms is only possible through the use of methods, such as 15 N NMR relaxation, that are selectively sensitive to backbone motions. Recent studies have indicated that increases in protein conformational entropy upon ligand binding may help to stabilize protein-ligand complexes~Farrow et al, 1994;Stivers et al, 1996;Yu et al, 1996;Zidek et al, 1999!. Taken together with the present results, these studies suggest that regulation of protein entropy may be a rather widespread, albeit subtle, mechanism contributing to a variety of biochemical equilibrium processes.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, separation of the backbone entropy term from other terms is only possible through the use of methods, such as 15 N NMR relaxation, that are selectively sensitive to backbone motions. Recent studies have indicated that increases in protein conformational entropy upon ligand binding may help to stabilize protein-ligand complexes~Farrow et al, 1994;Stivers et al, 1996;Yu et al, 1996;Zidek et al, 1999!. Taken together with the present results, these studies suggest that regulation of protein entropy may be a rather widespread, albeit subtle, mechanism contributing to a variety of biochemical equilibrium processes.…”
Section: Discussionsupporting
confidence: 77%
“…Most residues that require the determination of s e to fit the model, with or without solute, are located in the loop. Similar behaviour has been observed in the loop regions or turns of E. coli topoisomerase I [52]. The average s e value for these high frequency motions is also left almost undisturbed by solute addition.…”
Section: Discussionsupporting
confidence: 76%
“…decrease in motion (or dynamics) (32). The experimental observation that binding can increase dynamics in some systems (20)(21)(33)(34)(35)(36)(37) emphasizes the importance of entropic contributions. The success of our approach in capturing this effect implies that the entropic contributions are adequately represented in the ensemble view as implemented by the COREX algorithm (6)(7)(8)(9).…”
Section: Resultsmentioning
confidence: 99%